Studi Kasus Putusan Nomor 245/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst Tentang Pengakuan Putusan Moratorium Pengadilan Singapura dalam Penyelesaian Cross-Border Insolvency dan Kaitannya terhadap Legal Standing Pemohon PKPU di Indonesia - Windy Riani Putri; Nyulistiowati Suryanti; Anita Afriana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to assess the legal considerations of the panel of judges in Decision Number 245/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst., particularly in recognizing the foreign court decision in the form of a moratorium ruling from the Singapore High Court and in determining the legal standing of the PKPU applicant in this case. This research employs a normative juridical method through a case study of Decision Number 245/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst based on Indonesian positive law. The data used consists of primary, secondary, and tertiary. Data analysis was conducted qualitatively by interpreting positive legal provisions, principles, and doctrines applicable in Indonesia to evaluate the panel of judges' considerations in this case. The research findings indicate that, first, the panel's recognition of the moratorium decision as grounds for rejecting the PKPU application contradicts Article 436 of the Reglement op de Rechtsvordering, which adheres to the territoriality principle. This recognition also conflicts with the principles of private international law adopted by Indonesia. Furthermore, the consideration regarding the absence of legal standing of the PKPU applicant due to the existence of the moratorium decision linked to choice of forum is inconsistent with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (KPKPU Law) as lex specialis that supersedes debt settlement provisions in other legislation. Second, the research demonstrates that in practice, legal standing is determined based on fulfillment of formal and material requirements as stipulated in Articles 222, 224, and 8(4) of the KPKPU Law, which were satisfied in this case.